2022
DOI: 10.1002/dev.22233
|View full text |Cite
|
Sign up to set email alerts
|

Infant posture and caregiver‐provided cognitive opportunities in typically developing infants and infants with motor delay

Abstract: Infants’ developing motor skills—including mastery of new postures such as sitting and standing—affect opportunities for learning that facilitate cognitive development. But how infant posture affects caregiver behavior is largely unexplored. Moreover, we know little about effects of posture on learning opportunities in infants with motor delay. This study asked how infants with typical development and infants with significant motor delay use various postures during play, and whether posture is related in real … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Indeed, infants’ evolving repertoires for action appear to spill over into their interactions with caregivers which in turn, results in new opportunities for development (see Iverson, 2021). When infants sit independently, for example, they are able to explore objects in more sophisticated ways (Soska et al., 2014), are more likely to receive opportunities for cognitive stimulation from their caregivers (Kretch et al., 2022), and more frequently engage in joint attention (Franchak et al., 2018). Thus, it is not surprising that research has uncovered longitudinal relations between sitting, spatial memory, and language (spatial and receptive; Libertus & Violi, 2016; Oudgenoeg‐Paz et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, infants’ evolving repertoires for action appear to spill over into their interactions with caregivers which in turn, results in new opportunities for development (see Iverson, 2021). When infants sit independently, for example, they are able to explore objects in more sophisticated ways (Soska et al., 2014), are more likely to receive opportunities for cognitive stimulation from their caregivers (Kretch et al., 2022), and more frequently engage in joint attention (Franchak et al., 2018). Thus, it is not surprising that research has uncovered longitudinal relations between sitting, spatial memory, and language (spatial and receptive; Libertus & Violi, 2016; Oudgenoeg‐Paz et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Can you make them spin? Push the car and make them spin!”) when infants are sitting relative to all other postures (e.g., supine, prone; Kretch et al, 2022). This suggests that caregivers are sensitive to the new possibilities for engagement that are presented by a sitting infant.…”
Section: Advances In Posture and Language Development: The Transition...mentioning
confidence: 99%
“…They interact variously with objects, people, and their environments [9,10]. Postural control in sitting also enables the interaction promoting face-to-face exchange and joint attention with their caregivers [11].…”
Section: Postural Control and Sittingmentioning
confidence: 99%
“…Kretch et al [11] demonstrated that caregivers were most likely to provide learning opportunities when infants were sitting. Their findings suggest that early intervention should focus on improving postural control.…”
Section: Postural Control and Sittingmentioning
confidence: 99%